Peran Guru dalam Membentuk Karakter Religius Anak Usia Dini di TK Islam Al Azhar 43 Gorontalo - Arthika Rahmawati Ilam; Lestari B. Samaun; Meiranti Saputri S. Djawalu; Sucitra Muharam (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to describe the role of teachers in shaping the religious character of early childhood at Al Azhar 43 Gorontalo Islamic Kindergarten. A descriptive qualitative approach is used to understand the teacher's strategy in guiding children through exemplary, habituation, motivation, and contextual learning. The results showed that teachers play a central role as role models, facilitators, mentors, and motivators in the formation of children's religious character. Routine activities such as praying together, habituation of greetings, and worship practices are effective ways to introduce religious values to children. In addition, collaboration between teachers, parents and educational institutions strengthens the learning of religious values both at school and at home. A supportive environment and consistent involvement of all parties are the keys to successful religious character building in early childhood. This research is expected to be a reference in the development of religious character education in early childhood education institutions.